Activist Evaluation - Michael Scriven (The Evaluation Center at Western Michigan University, 2007)
To what extent should the evaluator be an active agent in the events surrounding or incorporating or following whatever s/he is evaluating? This question comes up to haunt us in the field from time to time and it does not have an easy answer. It is part of a larger methodological question about proactive versus reactive research. The term 'participant observer' reminds us that even the observer's role has been, rightly or wrongly, avoidably or unavoidably, sometimes blurred into the participant's role. And the evaluator is often more 'involved' in events than the observer, because in formative evaluation, or even in summative evaluation that will be published, what the evaluator is doing will often have some direct effect on what happens thereafter.